BROADENING THE SCOPE OF DEBATES AROUND STEM CELL RESEARCH. (16th April 2012) - LYSAGHT, TAMRA; CAMPBELL, ALASTAIR V.
ABSTRACT Over the last decade, stem cell research has generated an enormous amount of public, political and bioethical debate. These debates have overwhelmingly tended to focus on two moral issues: the moral status of human embryos and the duty to care for the sick and vulnerable. This preoccupation, especially on the question of moral status, has not only dichotomized the debate around two fundamentally incommensurable positions, it has come at the cost of other important issues largely being ignored. In highlighting some of the bioethical and regulatory deficiencies of this fixation, we draw on recent developments in the experimental use of autologous adult stem cells to argue for a more inclusive approach to the ethical issues surrounding stem cell research.